Design and Analysis of Machine Learning Algorithms for the Reduction of Crime Rates in India: An analysis of machine learning algorithms for reducing crime rates in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Crime has a negative impact on economic development since it keeps rising day by day. Reducing crime has become a top priority in our society since it is such a serious problem. As a result, figuring out what influences crime rates and how to do it in the most effective manner is critical. In order to do this, a database must be kept, which records various crimes with information relating to location, time, and nature, among other things, for future use. Using machine learning algorithms to minimize crime in India is the subject of this study. Finding patterns in large datasets has never been simpler thanks to advances in machine learning. Predicting the sort of crime that will occur in a given area is the primary goal of this study. Through the use of clean and transformed training data sets, machine learning has been utilized to construct a model. Data visualization may be used to do analysis on a data collection and its features. Factors of the situation are being analyzed and documented. In order to keep society secure, risk variables have been discovered and prediction techniques have been devised. This research included clustering algorithms, optimization techniques, and statistical analysis.